1993
DOI: 10.1021/j100104a017
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength effects in the photolysis of ketones: stereoisomerization and magnetic isotope carbon-13/carbon-12 separation; a probe for adiabatic versus diabatic trajectories during bond dissociation

Abstract: The I3C enrichment in the photolysis of three ketones, dibenzyl ketone (DBK), (S)-(+)-a-methyldeoxybenzoin (MDB), and d,l-2,4-diphenylpentan-3-one (DPP), along with the photostereoisomerization of the latter two From the simple paradigm of eq 1, the value P,, the probability of combination of a primary geminate pair, is a potentially useful and intuitive mechanistic parametcfl~~ which clearly represents the competition between the knit process and all other competing processes.When the primary geminate pair is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Step et al 35 have studied the wavelength effects on the stereoisomerization and 13C/12C isotope separation under the photolysis of three ketones, methyldeoxybenzoin (MDB), dibenzyl ketone (DBK), and 2,4-dimethylpentanone (DPP) in SDS micelles. By monitoring the circular dichroism for MDB and DPP and by measuring isotope distribution for all ketones, a and RP recombination probabilities P have been evaluated.…”
Section: Direct Kinetic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Step et al 35 have studied the wavelength effects on the stereoisomerization and 13C/12C isotope separation under the photolysis of three ketones, methyldeoxybenzoin (MDB), dibenzyl ketone (DBK), and 2,4-dimethylpentanone (DPP) in SDS micelles. By monitoring the circular dichroism for MDB and DPP and by measuring isotope distribution for all ketones, a and RP recombination probabilities P have been evaluated.…”
Section: Direct Kinetic Methodsmentioning
confidence: 99%
“…Only the central part of the DBK molecule, -CH2COCH2-, should be taken into consideration, since in the precursor RP (PhCH2* 'COC^Ph), HFI is significant and, therefore, strongly influences the RP spin dynamics only for CH2 and COCH2 groups in the radical partners, while all other HFI couplings can be ignored. For each isotopic modification i of DBK listed above (i = 1 -6) eq 28 acquires the form = ln(l -F^/lnd -Ft) (35) where Fi and Ft are the conversions of the first (isotopically nonlabeled) and ith isotopic forms, respectively. The concentration of any isotopic form can be obtained from the relation C; = Ufi (36) where C is the total concentration of DBK molecules and coefficients Ui are determined statistically from the isotope distribution:…”
Section: Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…confirmed it in triplet sensitized photolysis of benzoyl peroxide. Nicholas Turro in 1978 was the first who used micelles as the microreactors for the photolysis reactions; he has shown that the reactions in micelles result in enormously large isotope separation. In 1980 Pines and co-workers showed that in viscous solutions the magnetic isotope effect markedly increases (see, for details, ref ). Later this nuclear spin and, therefore, nuclear magnetic moment dependent isotope effect was discovered for oxygen, silicon, , sulfur, , germanium, , tin, mercury, , magnesium, , calcium, zinc, and uranium .…”
Section: Short History Of Miementioning
confidence: 99%
“…Later, MIE was found in the photolysis of DBK on porous silica and zeolites and in the photolysis of phenyl adamantyl ketone and many others, including cyclic ketones . Temperature and wavelength effects on the MIE in the photolysis of ketones have also been studied (section 5).…”
Section: Mie:  the Road Of Discoveriesmentioning
confidence: 99%